Antiaging Property and Mechanism of Phase-Change Asphalt with PEG as an Additive. (23rd November 2020) - Wang, Huiru; Wang, Yanmin; Li, Xian; Chen, Min; Wu, Yanling; Sun, Cuicui; Wang, Xiaoning
Abstract : In this study, phase-change asphalt was prepared with polyethylene glycol (PEG-1000) as a modifier. The short- and long-term antiaging performances were characterized by rolling-thin-film-oven (RTFOT) and pressure-aging vessel (PAV) tests, respectively. The functional groups and "bee structures" of PEG-modified asphalt and base asphalt were characterized by Fourier transform infrared absorption spectroscopy (FTIR) and atomic force microscopy (AFM). The research results indicate that the additive of PEG can improve the high-temperature, temperature sensitivity, and the antiaging properties of asphalt. The FTIR reveals that only physical blending and no chemical reaction occurs between PEG and asphalt. AFM topography indicates that smaller "bee structures" appear on the surface of PEG-modified asphalt and these structures do not change during aging.